Identification of protein kinase C domains involved in its translocation induced by propofol - Narasaki, Soshi; Noguchi, Soma; Urabe, Tomoaki; Harada, Kana; Hide, Izumi; Tanaka, Shigeru; Yanase, Yuhki; Kajimoto, Taketoshi; Uchida, Kazue; Tsutsumi, Yasuo M.; Sakai, Norio (European journal of pharmacology, 2023)
Propofol is widely used for general anesthesia and sedation; however, the mechanisms of its anesthetic and adverse effects are not fully understood. We have previously shown that propofol activates protein kinase C (PKC) and induces its translocation in a subtype-specific manner. The purpose of this study was to identify the PKC domains involved in propofol-induced PKC translocation. The regulatory domains of PKC consist of C1 and C2 domains, and the C1 domain is subdivided into the C1A and C1B subdomains. Mutant PKCα and PKCδ with each domain deleted were fused with green fluorescent protein (GFP) and expressed in HeLa cells. Propofol-induced PKC translocation was observed by time-lapse imaging using a fluorescence microscope. The results showed that persistent propofol-induced PKC translocation to the plasma membrane was abolished by the deletion of both C1 and C2 domains in PKCα and by the deletion of the C1B domain in PKCδ. Therefore, propofol-induced PKC translocation involves the C1 and C2 domains of PKCα and the C1B domain of PKCδ. We also found that treatment with calphostin C, a C1 domain inhibitor, abolished propofol-induced PKCδ translocation. In addition, calphostin C inhibited the propofol-induced phosphorylation of endothelial nitric oxide synthase (eNOS). These results suggest that it may be possible to modulate the exertion of propofol effects by regulating the PKC domains involved in propofol-induced PKC translocation. •Propofol. a general anesthetic, induced the translocation of PKCαand PKCδ.•Both C1 and C2 domains were required for propofol-induced PKCα translocation.•The C1B domain was critical for propofol-induced PKCδ translocation.•Calphostin C, a C1 domain inhibitor, abolished propofol-induced PKCδ translocation.